2011
DOI: 10.1074/jbc.m110.206755
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles of Group X-secreted Phospholipase A2 in Reproduction, Gastrointestinal Phospholipid Digestion, and Neuronal Function

Abstract: Although the secreted phospholipase A 2 (sPLA 2 ) family has been generally thought to participate in pathologic events such as inflammation and atherosclerosis, relatively high and constitutive expression of group X sPLA 2 (sPLA 2 -X) in restricted sites such as reproductive organs, the gastrointestinal tract, and peripheral neurons raises a question as to the roles played by this enzyme in the physiology of reproduction, digestion, and the nervous system. Herein we used mice with gene disruption or transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 88 publications
(165 reference statements)
2
35
0
Order By: Relevance
“…1 and 2 ) ( 64,70,74,112,121,132,134,135 ). It is now obvious that individual sPLA 2 s play unique and tissue-specifi c roles by acting on extracellular phospholipids, which include adjacent cell membranes, noncellular lipid components, and foreign phospholipids, such as those in microbes and food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and 2 ) ( 64,70,74,112,121,132,134,135 ). It is now obvious that individual sPLA 2 s play unique and tissue-specifi c roles by acting on extracellular phospholipids, which include adjacent cell membranes, noncellular lipid components, and foreign phospholipids, such as those in microbes and food.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, polymorphisms in the PLA2G10 gene are linked to a decreased risk of recurrent cardiovascular events ( 125 ), or not associated with plasma sPLA 2 activity or with coronary heart disease risk ( 126 ). Additionally, in different studies, Pla2g10 Ϫ / Ϫ mice display altered or unaltered macrophage functions ( 127 ) or increased or decreased adiposity ( 121,128 ). Although some of these studies were performed under the assumption that sPLA 2 -X is expressed in macrophages or adipocytes, our own investigations have shown that its expression in these cells is low or almost undetectable.…”
Section: Pla2g5/spla 2 -Vmentioning
confidence: 99%
“…Unlike sPLA 2 -V, however, sPLA 2 -X does not infl uence the Th2 response itself, because antigen-sensitized Pla2g10 Ϫ / Ϫ and wild-type mice have similar IgE and IL-4 levels ( 94 ). Pla2g10 Ϫ / Ϫ mice are also protected from myocardial infarction or aneurysm (118)(119)(120), show a reduced infl ammatory pain ( 121 ), have an increased adrenal steroidogenesis ( 122 ), and exhibit alteration in insulin secretion by pancreatic ␤ cells, perhaps as a result of reduced prostaglandin E 2 (PGE 2 ) synthesis ( 123 ). However, several of the phenotypes reported for Pla2g10 Ϫ / Ϫ mice are controversial.…”
Section: Pla2g5/spla 2 -Vmentioning
confidence: 99%
“…sPLA 2 -X is released from activated sperm cells during the acrosome reaction. Pla2g10 Ϫ / Ϫ spermatozoa display a poorer acrosome reaction and lower fertility, despite showing normal maturation and motility ( 121,132 ). Thus, sPLA 2 -X, a "reproductive sPLA 2 ," plays a specifi c role in sperm activation, boosting the acrosome reaction probably through production of some lipid products from sperm membranes in a paracrine or autocrine manner.…”
Section: Pla2g12/spla 2 -Xii Subfamilymentioning
confidence: 99%
“…2. POTENTIAL ROLES OF sPLA 2 s: LESSONS FROM sPLA 2 TRANSGENIC MICE Some of the biological actions of sPLA 2 s in vivo have been addressed using sPLA 2 -overexpressing TG mice, which have provided informative insights into the potential pathophysiological roles of sPLA 2 s (Ait-Oufella et al, 2013;Cash, Kuhel, Goodin, & Hui, 2011;Curfs et al, 2008;Grass et al, 1996;Ivandic et al, 1999;Laine, Grass, & Nevalainen, 1999;Mulherkar et al, 2003;Ohtsuki et al, 2006;Sato et al, 2011Sato et al, , 2008Sato et al, , 2009Taketomi et al, 2013;Yamamoto et al, 2015Yamamoto et al, , 2011. In this section, we briefly summarize general aspects, rather than describing individual topics in detail, of sPLA 2 -TG mice.…”
mentioning
confidence: 99%